Strategy for strengthening the characteristics of students in tsanawiyah madrasa - Abdul Rahim Karim; Arifuddin (Sao Literasi Publisher, Yayasan Pendidikan Khaerul Munif, 2022)
This study aims to reveal how the teacher's strategy in strengthening the character of students at State Tsanawiyah Madrasa in Palopo. The research approach used to answer this research problem is qualitative, with the type of case study research. Data collection techniques used participant observation, semi-structured interviews, and documentation studies. The data analysis technique used a modified analytical induction technique and Miles, Huberman, and Saldana interactive model data analysis technique, as well as checking the validity of the data through credibility (triangulation technique), dependability, confirmability, and transferability. The results of this study can provide an understanding that the teacher's strategy in strengthening the character of students is carried out by instilling religious values ​​through a personal approach, providing endless motivation, being a good role model, and providing positive suggestions through habituation. In addition, some factors support the teacher's strategy in strengthening the character of students such as factors of educational institutions under the auspices of the Ministry of Religion, strict rules, professional teachers in the learning process, family support for students, and complete educational unit facilities and infrastructure.